Management of Farmer-herdsmen Conflicts in North Central Nigeria: Implications for Collaboration between Agricultural Extension Service and other Stakeholders - Rashid Solagberu Adisa (Journal of International Agricultural and Extension Education, 2011)
Incessant resource-based conflicts between farmers and herdsmen continue to undermine the impact of agricultural extension service delivery in Nigeria. This study focuses on the perceptions of conflict and coping strategies among farmers and herdsmen towards identifying a role for Extension in management of farmer-herdsmen conflict. Multi-stage cluster random sampling technique was used to select 300 farmers and 60 cattle herdsmen for the research, using an interviewer-administered questionnaire for data elicitation. Most farmers (78%) perceived the conflict situation as a ‘loss’, while 68% of herdsmen perceived it as ‘threat’. Also, 75% of farmers used ‘problem-oriented’ coping strategies, while 73% of herdsmen mainly used ‘emotion-oriented’ coping strategies. Sixty-two percent of farmers and 7% of herdsmen alternatively used ‘social-support’ strategies. Pearson correlations showed that annual income (r=0.773, p=0.001), farm size (r=0.82, p=0.002), non-farm income (r= -0.71, p=0.003) and household size (r=0.651, p=0.004) were the significant correlates of loss perception among farmers; while among herdsmen, the significant correlates of threat perception were age (r=0.611, p=0.033) and herd size (r=0.814, p=0.002). Furthermore, only 4% of total respondents perceived the conflict situation as ‘opportunity to gain’. The paper concludes that farmer-herdsmen conflicts in Nigeria need not become inflexible as they currently seem, and suggests the setting up of a three-tier farmer-herdsmen conflict management committee. The paper recommends a functional role for Extension in periodic revision and enhanced awareness of and compliance with stock routes, as well as Extension staff and clientele training on appropriate coping mechanisms to douse the socio-psychological effects of conflicts.
Keywords: Farmer-herdsmen conflicts; management; extension; collaboration; coping